INFLUENCE OF PLANT ANTHELMINTICS ERLIM AND EKORSOL ON MORPHOMETRY OF HEPATOCYTE NUCLEI IN HAMSTERS WITH INDUCED OPISTHORCHIASIS - LYUBOV V. Natcheva; YULIYA A. Nesterok (Фундаментальная и клиническая медицина, 2017)
Aim. To study morphometry of hepatocyte nuclei in hamsters with induced opisthorchiasis after the treatment with plant anthelmintics Erlim and Ekorsol. Materials and Methods. Syrian hamsters (Mesocricetus auratus) were divided into 4 groups: 1) without experimentally induced opisthorchiasis and treatment; 2) with opisthorchiasis and without treatment; 3) with opisthorchiasis and treatment using Erlim (0.023 g/kg body weight for 5 days); 4) with opisthorchiasis and treatment using Ekorsol (0.26 g/kg body weight for 5 days). Infectious dose was 100 metacercariae per animal, treatment with Erlim or Ekorsol was started 90 days postinfection. After 14 days of treatment, the animals were sacriced with a subsequent liver explantation and histological examination (300 slides per group). Morphometric analysis was performed employing Aperio ImageScope package. Results. Ranges of hepatocyte nuclei in the groups of healthy untreated, Erlim- and Ekorsol-treated hamsters were 9.62, 8.91, and 6.64 u.e., respectively. Therefore, treatment with Erlim but not with Ekorsol induced proliferation and regeneration of liver tissue. Conclusions. Erlim is more efficient plant anthelmintic compared to Ekorsol.